Empowered by the Spirit of Yahweh: A Study of Micah 3:8 - Wessels, Wilhelm J. (Journal of Biblical & Pneumatological Research, 2009)
The article presents a study on Micah 3: 8 which tackled the function of power and leadership in the Israel and Judah societies. It notes that religious power is necessity which will result to danger and conflict if abused. It mentions that the book of Micah portrayed powerlessness and power abuse in the Jews society. The book of Micah states that religious power must promote justice and righteousness in the society. Moreover, chapter 3 of the book of Micah also cited that the religious adherents who are denied by Yahweh are powerless to perform prophetic ministry against the Spirit of Yahweh's prophet.
Paid
Keywords: ISRAEL; JUDAEA (Region); JUDAISM; JUSTICE; LEADERSHIP – Religious aspects; MICAH (Biblical prophet) – In rabbinical literature; NAME of God in Judaism; POWER (Christian theology); PROPHETS in the New Testament; RELIGION; RELIGIOUS adherents; SELF-efficacy; SPIRIT